11.7 A multimodality CMOS sensor array for cell-based assay and drug screening - Jong Seok Park; Taiyun Chi; Butts, Jessica; Hookway, Tracy; McDevitt, Todd; Hua Wang (2015 IEEE International Solid State Circuits Conference (ISSCC), 2015)
Cell-based assays are powerful tools to characterize cell- or tissue-specific physiological behaviors under external biochemical stimuli. External biochemical stimuli trigger endogenous cellular mechanisms that produce a cascade of physiological changes, resulting in easily measurable signals. Cell-based assays are widely used for large-scale drug screening in the pharmaceutical industry, where in vitro cultured cells are used to characterize the potency and toxicity of thousands of chemicals, leading to new drug development. This is particularly relevant in individualized medicine as patient-derived cells can test personalized drug responses. However, most current cell-based assays are conducted on single-modality sensors (electrical or optical only), which cannot capture the complexity of multi-parameter physiological responses. Sequentially transporting cell samples through different sensor platforms results in low throughput and potential abrogation of cell functions, while parallel monitoring of multiple samples with different modalities is subject to cell-to-cell variation even in a homogeneous cell population.